New Diagnosis of AIDS Based on Salmonella enterica subsp. I (enterica) Enteritidis (A) Meningitis in a Previously Immunocompetent Adult in the United States. (14th August 2017) - Elton, Andrew C.; Levin, James; Lazio, Matthew P.
Abstract : Salmonella meningitis is a rare manifestation of meningitis typically presenting in neonates and the elderly. This infection typically associates with foodborne outbreaks in developing nations and AIDS-endemic regions. We report a case of a 19-year-old male presenting with altered mental status after 3-day absence from work at a Wisconsin tourist area. He was febrile, tachycardic, and tachypneic with a GCS of 8. The patient was intubated and a presumptive diagnosis of meningitis was made. Treatment was initiated with ceftriaxone, vancomycin, acyclovir, dexamethasone, and fluid resuscitation. A lumbar puncture showed cloudy CSF with Gram negative rods. He was admitted to the ICU. CSF culture confirmed Salmonella enterica subsp. I ( enterica ) Enteritidis (A). Based on this finding, a 4th-generation HIV antibody/p24 antigen test was sent. When this returned positive, a CD4 count was obtained and showed 3 cells/mm 3, confirming AIDS. The patient ultimately received 38 days of ceftriaxone, was placed on elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide (Genvoya) for HIV/AIDS, and was discharged neurologically intact after a 44-day admission.